Valuation effects of U.S. monetary policy tightening: The roles of foreign exposure - Xin Fang; Xingyue Peng (PLoS ONE, 2026)
Starting in 2022, the United States launched a new round of monetary policy tightening, adopting a dual-track strategy of sustained interest rate hikes and balance sheet reduction. These measures have generated significant spillover effects on China’s stock market. Against this backdrop, this paper employs an event study and regression analysis to investigate the short-term market response of Chinese A-share listed firms to U.S. monetary tightening shocks. The analysis captures firms’ overseas exposure from three dimensions—trade, investment, and financial channels. Empirical results reveal that trade exposure is positively associated with cumulative abnormal returns (CARs), while both investment and financial exposures exert significant negative effects. The paper further discusses the differentiated moderating mechanisms of managerial resource allocation capacity and VC background across the three types of overseas exposures. Heterogeneity analysis shows that the influence of overseas exposure on market performance varies by firms’ technological intensity. Firms with high investment exposure—particularly those involved in foreign ownership, cross-border M&A, and greenfield investment—perform worse under policy shocks.